Air Quality Study in Mijen District, Semarang City in 2022 - Ristiyani Cahyaningrum; Yuni Wijayanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
The higher the air pollution in an area, the more it can have a negative impact on human health status if inhaled continuously, especially in the respiratory system. This study used secondary data obtained from the Environment and Forestry Service. The data was analyzed using a descriptive method by comparing data collected in the field with ambient air quality standards based on Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management to determine air quality conditions in Mijen District, Semarang City. The impact resulting from air pollution can interfere with the health of living things and damage the ecosystem environment. Human health will be disrupted due to polluted air, which can lead to diseases such as ARI, heart disease, and even lung cancer, which is very dangerous. For this reason, it is necessary to conduct research on air quality to prevent air pollution that exceeds ambient air quality standards, which can cause health problems for the community in Mijen District. Based on research on the analysis of air quality parameter measurement results in Mijen District, Semarang City, it can be concluded that all air quality parameters do not exceed quality standards.